Early Miocene intensification of the North African hydrological cycle: multi-proxy evidence from the shelf carbonates of Malta - Geochemical data - Raymond Zammit (PANGAEA, 2022)
A total of 140 samples were collected from the il-Blata section outcropping on the Mediterranean Island of Malta (base of section at 35.9004N, 14.3309E, top of section at 35.9000N, 14.3314E). 16 of these samples were selected to determine the 87Sr/86Sr in the bulk sediment and used to generate numerical ages using the LOWESS FIT for Sr-Stratigraphy (McArthur et al., 2012). All 87Sr/86Sr measurements conducted at the University of Geneva using a Thermo Neptune PLUS Multi-Collector inductively coupled plasma mass spectrometer. Data and numerical age model presented in table S1. The εNd data from (Bialik et al., 2019) were recalibrated to fit the new age model and presented in table S2. The percentage carbonate matter was measured using a FOGl digital calcimeter at the University of Malta (table S3). Dry powders were used to generate a stable isotope (δ18O & δ13C) record (table S4), all measurements were conducted on a Gasbench II coupled to a Thermo Delta V Advantage isotope ratio mass spectrometer at the School of Earth and Environmental Sciences, Cardiff University. Dry bulk sediment powders were also used to obtain major element composition and calculate element ratios Sr/Ca, Ti/Al, K/Al, Zr/Al, Si/Ti. All element measurements were conducted at The School of Earth and Environmental Sciences, Cardiff University using a hand-held Olympus Delta Innov-X XRF gun. Element data presented in table S5. Mean values of the ratios Sr/Ca, Ti/Al, K/Al, Zr/Al and Si/Ti were obtained for three different parts in the section in order to determine regime changes (table S6).